Climbing games : challenge and train your hands, feet, body and brain with over 120 activities. - Smith, Paul, ....- (Caernarfon : Pesda, 2009)
Challenge and train your hands, feet, body and brain with over 120 climbing games. This book is for anyone wanting to have fun climbing while developing crucial skills. The games described can be used in a wide range of activities from working on specific skills to fun warm-ups. As an aid to a climbing session or as the sole activity, climbing movements can be broken down and practised in a safe but challenging environment.The book takes an introductory look at which specific aspects of climbing and methods of coaching are important - together with some aspects of sports science, this give the text a dual purpose as a coaching manual and as an encyclopaedia of games.Many of these games are particularly suited to those that are new to climbing and wish to improve their skills. If you're new to climbing, you'll find games which introduce some essential skills (such as 'crimping' a hold). Equally, old hands may welcome new games as an aid to helping friends progress or as an addition to a weekly climbing session.As a qualified instructor or an informal coach teaching friends or a parent teaching their children, this book provides an invaluable tool for hours of practical training or even just entertainment for rainy afternoons! The easy to use format allows those coaching or even the client themselves to select their own games based on current needs and desires. The overview of skills employed in each game will help you turn play into progress.
Keywords: Klimsport